Massive Galaxies in Cosmological Simulations: Ultraviolet-selected Sample at Redshift z = 2 - Nagamine, Kentaro; Cen, Renyue; Hernquist, Lars; Ostriker, Jeremiah P; Springel, Volker (The Astrophysical journal, 2005)
We study the properties of galaxies at redshift z = 2 in a cold dark matter ( CDM) universe, using two different types of hydrodynamic simulation methods--Eulerian total variation diminishing (TVD) and smoothed particle hydrodynamics (SPH)--and a spectrophotometric analysis in the U sub(n), G, R filter set. The simulated galaxies at z = 2 satisfy the color-selection criteria proposed by Adelberger et al. and Steidel et al. when we assume Calzetti extinction with E(B - V) = 0.15. We find that the number density of simulated galaxies brighter than R < 25.5 at z = 2 is about 2 x 10 super(-2) h super(3) Mpc super(-3) for E(B - V) = 0.15 in our most representative run, roughly 1 order of magnitude larger than that of Lyman break galaxies at z = 3. The most massive galaxies at z = 2 have stellar masses of 10 super(11) M sub( ), and their observed-frame G-R colors lie in the range 0.0 < G - R < 1.0. They typically have been continuously forming stars at a rate exceeding 30 M sub( )yr super(-1) over a few gigayears from z = 10 to z = 2, although the TVD simulation indicates a more sporadic star formation history than the SPH simulations. On the order of half of their stellar mass was already assembled by z 6 4. The bluest galaxies with colors -0.2 < G - R < 0.0 at z = 2 are somewhat less massive, with M sub(star) < 10 super(11) h super(-1) M sub( ), and lack a prominent old stellar population. On the other hand, the reddest massive galaxies at z = 2 with G - R . 1.0 and M sub(star) > 10 super(10) h super(-1) M sub( )completed the build-up of their stellar mass by z 6 3. Interestingly, our study indicates that the majority of the most massive galaxies at z = 2 should be detectable at rest-frame ultraviolet wavelengths, contrary to some recent claims made on the basis of near-infrared studies of galaxies at the same epoch, provided the median extinction is less than E(B - V) < 0.3 as indicated by surveys of Lyman break galaxies at z = 3. However, our results also suggest that the fraction of stellar mass contained in galaxies that pass the color-selection criteria used by Steidel et al. (2004) could be as low as 50% of the total stellar mass in the universe at z = 2. Our simulations imply that the missing stellar mass is contained in fainter (R > 25.5) and intrinsically redder galaxies. The bright end of the rest-frame V-band luminosity function of z = 2 galaxies can be characterized by a Schechter function with parameters (*, M sub(V)*, a) = (1.8 x 10 super(-3), -23.4, -1.85), while the TVD simulation suggests a flatter faint-end slope of a 6 -1.2. A comparison with z = 3 shows that the rest-frame V-band luminosity function has brightened by about 0.5 mag from z = 3 to z = 2, without a significant change in the shape. Our results do not imply that hierarchical galaxy formation fails to account for the massive galaxies at z 1.